2016
DOI: 10.1063/1.4968836
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz radiation generation and shape control by interaction of array Gaussian laser beams with plasma

Abstract: In the present paper, a scheme for generation of terahertz (THz) radiation in electron-neutral collisional plasma based on beating of two Gaussian laser array beams has been proposed. It is shown that the efficiency of THz radiation based on the Gaussian laser array beams can be enhanced drastically in comparison with the efficiency of THz radiation based on the Gaussian one. Furthermore, the producing THz radiation by the Gaussian laser array beams, which has an exclusive field profile, is affected by some ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Bakhtiari et al [116] proposed a scheme for improving terahertz radiation efficiency by the interaction of two Gaussian laser array beams in an electron-neutral collisional plasma. They optimized that high efficiency of up to 0.07% can be achieved using array beams, which is almost three times higher than the maximum efficiency achieved by a single Gaussian laser beam.…”
Section: Resonant Third Harmonic Generationmentioning
confidence: 99%
“…Bakhtiari et al [116] proposed a scheme for improving terahertz radiation efficiency by the interaction of two Gaussian laser array beams in an electron-neutral collisional plasma. They optimized that high efficiency of up to 0.07% can be achieved using array beams, which is almost three times higher than the maximum efficiency achieved by a single Gaussian laser beam.…”
Section: Resonant Third Harmonic Generationmentioning
confidence: 99%
“…These anisotropic phenomena can influence and also tune the electric field profile of EM waves propagating in an optically active medium. Nowadays, a large number of studies have been devoted to the harmonic generation in optically active media by nonlinear interaction of laser beams of different profiles [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Theoretical and experimental evidence indicates that the spatial profile of the laser beam plays a pivotal role in the electric field amplitude of generated radiation [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a large number of studies have been devoted to the harmonic generation in optically active media by nonlinear interaction of laser beams of different profiles [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Theoretical and experimental evidence indicates that the spatial profile of the laser beam plays a pivotal role in the electric field amplitude of generated radiation [16][17][18][19][20][21][22][23][24][25][26][27]. The nonlinear material properties are another important factor to consider in the new harmonic generation by intense laser-particle interaction [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The emission of THz radiation by beating two Gaussian pulsed laser beams in a rippled plasma with neutral-electron collision has been proposed by Bakhtiari et al [10] They observed that by optimizing the parameters of the laser beams, the collisional plasma, and the array structure, the efficiency of the radiation is enhanced to a considerable amount.…”
Section: Introductionmentioning
confidence: 99%